Antimicrobial activity of CdTe QDs modified with lanthanides on pseudomonas aeruginosa - Jelínková, Pavlína; Koudelková, Zuzana; Kopel, Pavel; Moulick, Amitava; Adam, Vojtěch (Mendel University in Brno, 2017)
The aim of this study is to obtain data based on an experimental procedure and check the effectiveness of some antibacterial agents against pathogenic bacteria. In the present experiment, two different nanoparticles (Cadmium Telluride Quantum dots with Lanthanides: Gadolinium and Terbium) were used to check their antibacterial properties on Pseudomonas aeruginosa. The Cadmium Telluride Quantum dots without the Lanthanides, Gadolinium nitrate and Terbium nitrate were also tested on those bacteria as control. In the present experiment, the following methods were employed: disc-diffusion test, the determination of the growth properties of the bacteria and comparison of absorbance after treatment with antimicrobial agent. From the results it has been found that the tested Cadmium Telluride Quantum dots with Lanthanides (Gadolinium and Terbium) have good antimicrobial effects. Additionally, GdQDs show stronger antibacterial effect than Tb QD and other tested compounds.

The aim of this study is to obtain data based on an experimental procedure and check the effectiveness of some antibacterial agents against pathogenic bacteria. In the present experiment, two different nanoparticles (Cadmium Telluride Quantum dots with Lanthanides: Gadolinium and Terbium) were used to check their antibacterial properties on Pseudomonas aeruginosa. The Cadmium Telluride Quantum dots without the Lanthanides, Gadolinium nitrate and Terbium nitrate were also tested on those bacteria as control. In the present experiment, the following methods were employed: disc-diffusion test, the determination of the growth properties of the bacteria and comparison of absorbance after treatment with antimicrobial agent. From the results it has been found that the tested Cadmium Telluride Quantum dots with Lanthanides (Gadolinium and Terbium) have good antimicrobial effects. Additionally, GdQDs show stronger antibacterial effect than Tb QD and other tested compounds.
Antimicrobial activity of CdTe QDs modified with lanthanides on pseudomonas aeruginosa
Keywords: Pseudomonas aeruginosa; antimicrobial activity; lanthanides; quantum dots; Pseudomonas aeruginosa; antimicrobial activity; lanthanides; quantum dots